Anticipatory effects in the FTSE 100 index revisions - Marcelo Fernandes; Jo\~ao Mergulh\~ao (Queen Mary University of London, School of Economics and Finance, 2015)
This paper examines the price impact of trading due to expected changes in the FTSE 100 index composition, which employs publicly-known objective criteria to determine membership. Hence, it provides a natural context to investigate anticipatory trading effects. We propose a panel-regression event study that backs out these anticipatory effects by looking at the price impact of the ex-ante probability of changing index membership status. Our findings reveal that anticipative trading explains about 40% and 23% of the cumulative abnormal returns of additions and deletions, respectively. The results are both statistically and economically significant.
Keywords: G12; G15; C14; 330; Imperfect substitutes; Index revision; Liquidity; Price pressure